FarmUSE: Assessment of antimicrobial use in pig farms - Ayebare, Dreck; Namuyomba, Maria Gonzaga; Muloi, M. Dishon; Eneku, Wilfred; Knight-Jones, Theodore J.D.; Moodley, Arshnee (International Livestock Research Institute, 2025)
Antimicrobial resistance (AMR) is an escalating threat to animal, human, and environmental health. In livestock production systems, antimicrobials are commonly used to prevent and control infectious diseases, particularly in settings characterized by weak biosecurity, high stocking densities, and limited access to veterinary services. Strengthening the measurement of antimicrobial use at the farm level is therefore critical for generating robust evidence to inform antimicrobial stewardship, surveillance systems, and evidence-based policy decisions.